That / Zero Variation in Private Letters and Drama (1420-1710): A Corpus-Based Approach - Cristina Suárez Gómez (Miscelánea: A Journal of English and American Studies, 2000)
This paper offers a description of the distribution of the complementisers that and zero in two informal registers of the language, namely, private letters and drama. The analysed texts date from the last period of Middle English and the whole of Early Middle English as represented in the computerised Helsinki Corpus of English Texts. In the first section the complement clauses and the complementisers found in the selected texts are analysed to discover their particular contexts of distribution. The second section, in turn, examines possible factors, both linguistic and extralinguistic, which may influence, and even condition, the choice of the complementiser.